Age alone is not a risk factor for periprosthetic joint infection. Issue 1 (September 2019) - Inoue, D.; Xu, C.; Yazdi, H.; Parvizi, J.
Summary: Background: It is not known whether age alone or the increased comorbidities in older patients are responsible for the higher rate of periprosthetic joint infection (PJI) in older patients. Aim: To test the hypothesis that age alone is not a risk factor for PJI after total joint arthroplasty. Methods: This retrospective study included the review of 23, 966 patients undergoing primary total hip and knee arthroplasty between January 1 st, 2010 and December 31 st, 2016 at a single institution. Patients who developed PJI, as defined by International Consensus Meeting criteria, were identified. All enrolled patients were divided into three groups that included patients aged <65 years ( N = 12, 761), 65–74 years ( N = 6850) and ≥75 years ( N = 4355). Using multivariate analysis and propensity score matching analysis, the possible association between age and PJI was examined. Findings: The incidence of PJI in the entire cohort was 0.72% (171 out of 23, 966). Multivariate analysis adjusting for all variables, except age, demonstrated that, compared to the patients aged <65 years, there was no statistically significant difference in the rate of PJI for patients aged 65–74 years (odds ratio: 0.89; 95% confidence interval: 0.55–1.42; P = 0.62) or for patients aged ≥75 years (0.69; 0.36–1.32; P = 0.26). Conclusion: When adjusting for confounding variables, age alone is not a risk factor for PJI. Studies evaluating the influence of age on the incidence of PJI should take into account the other confounding variables that contribute to PJI.